In the Name of Nationalism: A Feminist Security Critique on Indonesia's State Violence (1965-1999) - Jessenia Destarini Asmoro (Institute of International Studies, 2025)
This study analyses the gendered dimension of Indonesia’s idea of nationalism using feminist security perspective. Contested idea of nationalism had resulted in state securitization, conducted by Indonesia’s security forces in 1965-1999. However, this study found that such securitization did not take women’s security into account. The 1965-1966 political genocide, the military operations in Papua and Aceh, the 1998 May mass sexual violence, and the occupation in East Timor had shown that women were put in further insecurity than they already were. This can be seen from the fact that sexual violence with women as majority of the victims took place during those situations. As Indonesia’s social order was already a patriarchy, this gap of gender power relations became more affirmed when state securitization took place. Additionally, this study shows how Indonesia’s idea of nationalism reflects the subordination of women in the society.